Distribution. Subdivided into several isolated patches of different size: N sections located along Arctic shore in Russia from Northern Dvina River E to Kolyma River (Arkhangelsk Region, Nenets Autonomous District, SE Novaya Zemlya, Vaygach I, Northern Ural Mts, Yamal Peninsula, Belyy I, S Taymyr Peninsula, and N Yakutia), C section includes C Yakutia, and S sections extend from Kama River E to Amur River and from S Siberia S to Tian Shan and interfluve of Huang He and Yangtze in E China including Russia, ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. Subdivided into several isolated patches of different size: N sections located along Arctic shore in Russia from Northern Dvina River E to Kolyma River (Arkhangelsk Region, Nenets Autonomous District, SE Novaya Zemlya, Vaygach I, Northern Ural Mts, Yamal Peninsula, Belyy I, S Taymyr Peninsula, and N Yakutia), C section includes C Yakutia, and S sections extend from Kama River E to Amur River and from S Siberia S to Tian Shan and interfluve of Huang He and Yangtze in E China including Russia, Kazakhstan, Kyrgyzstan, Mongolia, and China (NW Xinjiang, Inner Mongolia [= Nei Mongol], Heilongjiang, Hebei, and Henan). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 322, DOI: 10.5281/zenodo.6707142 ...